Basics of qualitative research : techniques and procedures for developing grounded theory - Corbin, Juliet M., 1942-; Strauss, Anselm L. (Los Angeles : SAG, 2015)
Offering immensely practical advice, Basics of Qualitative Research, Fourth Edition presents methods that enable researchers to analyze, interpret, and make sense of their data, and ultimately build theory from it. Authors Juliet Corbin and Anselm Strauss (late of the University of San Francisco and co-creator of grounded theory) walk readers step-by-step through the research process - from the formation of the research question through several approaches to coding, analysis, and reporting. Packed with definitions and illustrative examples, this highly accessible book concludes with chapters that present criteria for evaluating a study, as well as responses to common questions posed by students of qualitative research. New end-of-chapter "Insider Insights" contributed by qualitative researchers give readers a sense of what it's like to work in the field. Significantly revised, this Fourth Edition remains a landmark volume in the study of qualitative methods.
Inspiration and background -- Theoretical foundations -- Practical considerations for getting started -- Prelude to analysis -- Strategies for qualitative data analysis -- Memos and diagrams -- Theoretical sampling -- Context -- Process -- Techniques for achieving theoretical integration -- The use of computer programs in qualitative data analysis -- Open coding: identifying concepts -- Developing concepts in terms of their properties and dimensions -- Analyzing data for context -- Bringing process into the analysis -- Integrating categories -- Writing theses, monographs, and dissertations, and giving talks -- About your research -- Criteria for evaluation -- Student questions and answers.
Includes bibliographical references and index.
Keywords: Social sciences -- Statistical methods